2017
DOI: 10.18203/2394-6040.ijcmph20174263
|View full text |Cite
|
Sign up to set email alerts
|

Health seeking behavior of farming community in rural area of Titabor block in Jorhat district

Abstract: Background: Numerous factors are associated with the access and utilization of health care services. These factors along with the preferences of the farmers are responsible for the health seeking behavior of farming community. This study aims to understand the health seeking behavior of the farmers and the factors influencing their behaviour in a rural block of Assam. Methods: A community based cross sectional study was done in a rural block of Jorhat district, Assam among a sample of 400 farmers. A pre design… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 6 publications
0
1
1
Order By: Relevance
“…In the present study the farmers preferred government and private facility equally in contrast to the study by Syeda S J, 7 and Rajesh R K 4 where majority of the farmers preferred government hospital.…”
Section: Discussioncontrasting
confidence: 88%
“…In the present study the farmers preferred government and private facility equally in contrast to the study by Syeda S J, 7 and Rajesh R K 4 where majority of the farmers preferred government hospital.…”
Section: Discussioncontrasting
confidence: 88%
“…As per a study conducted in the adjacent state of Assam, respiratory tract infections are identified as the primary cause of illness and death among agricultural workers. 21 Environmental factors also play a role in the development of respiratory ailments in agricultural environments, which may exacerbate cardiovascular health problems among this population. Without being statistically significant, comparisons between normal cultivators and jhum cultivators suggest possible discrepancies in health outcomes associated with diverse agricultural practices, animal waste, and other factors.…”
Section: Discussionmentioning
confidence: 99%